Granica i pogranicze polsko-niemieckie na forum Sejmu Rzeczypospolitej Polskiej w latach 1991-2004 = The German-Polish border and borderlands at the forum of the Sejm of the Republic of Poland in the years 1991-2004 - Glinka, Kamil (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The perspective of utilizing the fact that Poland and Germany are direct and peaceful neighbors, as well as specifying the planes and mechanisms of a double-sided cooperation in the borderland region was the main subject of interest of the Sejm membership during the 1st, 2nd, 3rd, and 4th term of office. In the effect, the issue was often raised on the forum of the lower house of the Polish Parliament and shaped the character of the debates concerning the broadly-understood Polish-German relation development.
Keywords: czasopismo; czasopismo akademickie; Ziemie Zachodnie; stosunki polsko-niemieckie; pogranicze polsko-niemieckie; historia